Molecular characterization of colorectal mucinous adenocarcinoma and adenocarcinoma, not otherwise specified, identified by multiomic data analysis - Xu, Kailun; Zheng, Shu; Li, Baosheng; Shao, Yingkuan; Yin, Xiaoyang (Frontiers in Molecular Biosciences, 2023)
Adenocarcinoma not otherwise specified (AC) and mucinous adenocarcinoma (MC) have different biological behaviors and clinical features. We utilized our previous proteomic data and public transcriptome, single-cell transcriptome, and spatial transcriptome databases to profile the molecular atlas of the tumor microenvironments of MC, AC and the normal colon tissues. By exploring the general and specific molecular features of AC and MC, we found that AC was immune-active but exposed to a hypoxic microenvironment. MC cells could protect against DNA damage, and the microenvironment was unfavorable to leukocyte transendothelial migration. We identified several potential molecular and cellular targets of AC and MC for future research. We also highlighted that the major difference between AC and MC was not the variety of cell types and functions but may be cell interactions. Stromal and epithelial cell interactions play important roles in both mucinous adenocarcinoma and adenocarcinoma not otherwise specified, but different regulatory pathways were involved.